2013
DOI: 10.1159/000350362
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Platelet Concentrates Using Dynamic Light Scattering

Abstract: Background: Each year, millions of platelet transfusions save the lives of cancer patients and patients with bleeding complications. However, between 10 and 30% of all platelet transfusions are clinically ineffective as measured by corrected count increments, but no test is currently used to identify and avoid these transfusions. ThromboLUX® is the first platelet test intended to routinely characterize platelet concentrates prior to transfusion. Methods: ThromboLUX is a non-invasive, optical test utilizing dyn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
35
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(38 citation statements)
references
References 27 publications
1
35
0
Order By: Relevance
“…22 Our results reflect this finding, with the cold-stored and cryopreserved PLTs having a lower score and fewer discoid PLTs than those stored at room temperature, as shown by microscopy. Traditionally, the Kunicki morphology score has been used to assess the number of discoid versus spherical PLTs in a sample.…”
Section: Discussionsupporting
confidence: 86%
See 3 more Smart Citations
“…22 Our results reflect this finding, with the cold-stored and cryopreserved PLTs having a lower score and fewer discoid PLTs than those stored at room temperature, as shown by microscopy. Traditionally, the Kunicki morphology score has been used to assess the number of discoid versus spherical PLTs in a sample.…”
Section: Discussionsupporting
confidence: 86%
“…In contrast, the DLS score combines all of these aspects, as well as the response to temperature stress to provide a score that has shown potential in estimating the in vivo efficacy of fresh liquidstored PLTs before transfusion. 22,39,40 While cold-stored PLTs had a lower DLS score than those stored at room temperature, all units maintained a score greater than 12, for up to 14 days of storage, which has been associated with better corrected count increments at 1 hour posttransfusion. 39,40 The lower score is likely partially reflective of the increase in microparticles, and while the algorithm assumes that microparticles are undesirable in PLT components, we have previously shown that they may actually provide a hemostatic benefit.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…The optical system, small sample volume, and specific software used in ThromboLUX address the challenges other DLS instruments face with testing platelet-rich plasma or platelet concentrates [20, 43]. The qNano Gold (Izon Science) uses size exclusion chromatography and resistive pulse sensing [47], and a combination of dynamic light scattering and particle tracking is used by NanoSight (Malvern) [48].…”
Section: Platelet Quality From the Perspective Of Productionmentioning
confidence: 99%